2009
DOI: 10.1111/j.1476-5381.2009.00404.x
|View full text |Cite
|
Sign up to set email alerts
|

NS11021, a novel opener of large‐conductance Ca2+‐activated K+ channels, enhances erectile responses in rats

Abstract: Background and purpose:  Large‐conductance Ca2+‐activated K+ channels (BKCa), located on the arterial and corporal smooth muscle, are potential targets for treatment of erectile dysfunction (ED). This study investigated whether NS11021 (1‐(3,5‐Bis‐trifluoromethyl‐phenyl)‐3‐[4‐bromo‐2‐(1H‐tetrazol‐5‐yl)‐phenyl]‐thiourea), a novel opener of BKCa channels, relaxes erectile tissue in vitro and enhances erectile responses in intact rats. The effects were compared with sildenafil, an inhibitor of phosphodiesterase t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
55
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(63 citation statements)
references
References 51 publications
7
55
1
Order By: Relevance
“…In the present study, we found that in primary HUVECs both SK Ca 3 and IK Ca channels were expressed, whereas BK Ca channel expression was undetectable. These findings agree with previous work in early passage HUVECs (Kestler et al, 1998) and our previous observations that an opener of BK Ca channels, 1-(3,5-bis-trifluoromethyl-phenyl)-3-[4-bromo-2-(1H-tetrazol-5-yl)-phenyl]-thiourea) (NS11021), does not change the currentvoltage relationship in early passage HUVECs (Kun et al, 2009). Furthermore, our patch-clamp studies in HUVECs indicated that the increased potassium conductance induced by NS309 was dependent on the presence of [Ca 2ϩ ] i and that it was inhibited partially by apamin and abolished by ChTX and TRAM-34, whereas it remained unaltered in the presence of IbTX.…”
Section: Discussionsupporting
confidence: 83%
“…In the present study, we found that in primary HUVECs both SK Ca 3 and IK Ca channels were expressed, whereas BK Ca channel expression was undetectable. These findings agree with previous work in early passage HUVECs (Kestler et al, 1998) and our previous observations that an opener of BK Ca channels, 1-(3,5-bis-trifluoromethyl-phenyl)-3-[4-bromo-2-(1H-tetrazol-5-yl)-phenyl]-thiourea) (NS11021), does not change the currentvoltage relationship in early passage HUVECs (Kun et al, 2009). Furthermore, our patch-clamp studies in HUVECs indicated that the increased potassium conductance induced by NS309 was dependent on the presence of [Ca 2ϩ ] i and that it was inhibited partially by apamin and abolished by ChTX and TRAM-34, whereas it remained unaltered in the presence of IbTX.…”
Section: Discussionsupporting
confidence: 83%
“…Relaxation of HCC induced by exposure to KCa activators has been demonstrated for NS1619 and another novel activator, NS11021 (Kun et al, 2009). In agreement with these findings, the KCa activators, NS-8 and NS1619, caused relaxation of HCC.…”
Section: Discussionsupporting
confidence: 78%
“…These reports are consistent with the present findings of the contribution of KCa to PDE5 inhibitor-induced vasodilatation of HPRA. The lack of influence of KCa blockade on relaxations driven by PDE5 inhibition in HCC is, however, in contradiction to the previously reported sensitivity of sildenafil-induced relaxation to IbTx in HCC (Kun et al, 2009), and the suggested participation of KCa in PDE5 inhibitor-induced relaxation in rabbit clitoris (Gragasin et al, 2004) and mouse corpus cavernosum (Werner et al, 2008). Our results nevertheless were strengthened by the absence of significant effects of NS-8 or NS1619 on sildenafil-induced relaxation of HCC.…”
Section: Figurecontrasting
confidence: 56%
See 1 more Smart Citation
“…Opening of BK Ca channels would be an alternative way of restoring an insufficient erectile function (e.g., Boy et al, 2004). Kun et al (2009) found that NS11021 (1-(3,5-Bis trifluoromethylphenyl)-3-[4-bromo-2-(1H-tetrazol-5-yl)-phenyl]-thiourea), a novel opener of BK Ca channels caused relaxation of both intracavernosal arteries and CC strips primarily through opening of BK Ca channels. It was also effective in facilitating erectile responses in anesthetized rats.…”
Section: B K ϩ Channelsmentioning
confidence: 99%